Factors Related to the Obedience of Hypertension Patients in Treating Treatment - Sirik, Maria Prisila; Littik, Serlie K.A.; Dodo, Dominirsep O. (Lontar : Journal of Community Health, 2023)
Hypertension is a condition of increasing a person's blood pressure beyond normal limits and causing an increase in morbidity and mortality. Compliance of hypertension patients to taking medication affects their blood pressure. This study aims to determine the factors related to the obedience of hypertension patients in undergoing treatment in the UPTD Working Area of ​​the Pasir Panjang Health Center, Kupang City. This study was an analytic observational study with a cross-sectional design. The population of this study amounted to 307 patients, with 59 respondents. The MMAS (Modified Morisky Adherence Scale) questionnaire measured obedience. The data were analyzed using the chi-square statistical test. The results showed that education (p=0.002; 95%CI=3.1652-4.8716), knowledge ((p=0.001; 95%CI= 5.1430-5.6691), family support (p=0.000; 95%CI= 3.4171-4.9020), and the role of health workers (p=0.003; 95%CI= 2.7915-7.4717), had a relationship with patient compliance. Hypertension in undergoing treatment. Gender, occupation, and health insurance participation were unrelated to compliance with hypertension sufferers undergoing treatment. The Puskesmas will likely provide media containing information about hypertension management in the examination room to increase public knowledge about hypertension. Families can play an active role in supporting hypertension patients to take medication and control blood pressure regularly.